HOW THE CANCER EXPERIENCE AFFECTS THE USAGE OF SPEECH ACTS IN LEBANESE ADOLESCENTS - Kfoury, Carla (Wacana: Jurnal Penelitian Bahasa, Sastra dan Pengajaran, 2022)
The aim of this study is to investigate the type of speech acts that Lebanese adolescents mostly use when talking about their experience with cancer. Generally, it is hard for people who have cancer to talk about their painful experience. More importantly, the whole experience could influence one’s choice of speech acts as well. Hence, the study attempts to identify speech acts in Lebanese adolescents' interview transcripts to further investigate how the illness experience could shape their choice of speech acts. The study uses a mixed model since it implements both the qualitative and quantitative method. Content analysis is implemented to identify speech acts in the interview transcripts based on Searle's (1969) and Yule's (1996) speech act theories. Quantitative analysis is implemented to account for the frequency of speech acts in the interview transcripts. The findings indicate that Lebanese adolescents mostly use expressive speech acts when talking about their experience with cancer. Expressive speech acts form 62% of the total percentage of speech acts in interview transcripts, followed by 38% of representative speech acts that are provided to convey facts or information. Regarding their attitude towards physicians, Lebanese adolescents tend to implement representative speech acts at 75% compared to 25% of speech act usage of expressives. The findings indicate the emotional involvement that Lebanese adolescents feel when depicting the hard moments they experience, the feelings of loss, and loneliness, as well the gratitude they express towards their supporting families. However, when expressing their attitude towards their physicians, emotional detachment prevails as adolescents use more representatives to provide information or facts about how physicians approach them. The present study could be further developed to investigate the attitudes of a larger sample of adolescents suffering from cancer as well as identifying the types of speech acts they use when talking about their experience with cancer. It could also lead to future suggestions and solutions that physicians could benefit from to enhance their relationship with their adolescent cancer patients and provide more support by implementing more expressive speech acts.